Effects of dietary chromium and zinc on egg production, egg quality, and some blood metabolites of laying hens reared under low ambient temperature - Şahin, Nurhan; Onderci, M; Şahin, Kazım (Springernature, 2002)
This experiment was conducted to evaluate the effects of chromium (chromium picolinate, CrPic) and zinc (ZnSO4.H2O) on egg production, egg quality, and serum insulin, corticosterone, glucose, cholesterol, and total protein concentrations of laying hens reared under a low ambient temperature (6.8degreesC). One hundred twenty laying hens (Hy-Line; 32 wk old) were divided into 4 groups, 30 hens per group. The laying hens were fed the control diet (T1) or the control diet supplemented with either 400 mug of Cr/kg of diet (T2), 30 mg of Zn/kg of diet (T3), or 400 mug of Cr plus 30 mg of Zn/kg of diet (T4). Although the dry matter intake (DMI) was similar (p > 0.05) for all treatment groups, supplemental chromium and zinc either individually or together increased live-weight change, egg production, and improved feed efficiency (p < 0.05). However, no significant differences were observed between T4 and T2 or T3. Compared to T1, supplemental chromium and zinc increased egg weight, eggshell weight, eggshell thickness, egg specific gravity, and Haugh unit (p < 0.05) in T2, T3, and T4 groups, among which there was no significant difference. Serum insulin concentration increased (p < 0.05) and corticosterone concentration decreased (p < 0.05) with dietary chromium and zinc supplementation. Serum glucose and cholesterol concentrations decreased (p < 0.05) and protein concentrations increased (p < 0.001) with dietary chromium and zinc supplementation in all treatment groups. The results of this study indicated that either supplemental dietary chromium or zinc increased plasma insulin and decreased corticosterone concentrations and that had a positive effect on performance of laying hens under low ambient temperature.
Keywords: cold stress; chromium; zinc; egg; insulin; corticosterone; laying hen